2009
DOI: 10.1080/14766080902815148
|View full text |Cite
|
Sign up to set email alerts
|

“The strangers within our gates”: managing visitors at Temple Square

Abstract: While religious travel to religious sites has existed for millennia, only recently has this phenomenon been examined by tourism scholars. Within the research on religious site management, the empirical nature of the organizational and operational management of sacred sites has been understudied in the tourism management literature.The purpose of this paper is to correct this deficiency by examining the management structure and practices at Temple Square, the spiritual center of The Church of Jesus Christ of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The purpose of this paper was to look at not just the 'how' but also to understand the 'why' behind the methods and content of site interpretation at Temple Square in Salt Lake City, Utah. Managing non-Mormon visitors to Temple Square was the first foray of the Latter-day Saint Church into catering to the diverse motivations and expectations of tourists who came to Salt Lake City in the early Twentieth Century to learn more about and to gaze at the Latter-day Saints (see Eliason 2001;Gruen 2002;Hafen 1997;Olsen 2008Olsen , 2009. Over time, Church leaders have come to see tourism to Temple Square and its other historic sites in the United States as an avenue for outreach and proselytization (Hudman and Jackson 1992;Olsen 2006b, in press(b); Olsen and Timothy 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this paper was to look at not just the 'how' but also to understand the 'why' behind the methods and content of site interpretation at Temple Square in Salt Lake City, Utah. Managing non-Mormon visitors to Temple Square was the first foray of the Latter-day Saint Church into catering to the diverse motivations and expectations of tourists who came to Salt Lake City in the early Twentieth Century to learn more about and to gaze at the Latter-day Saints (see Eliason 2001;Gruen 2002;Hafen 1997;Olsen 2008Olsen , 2009. Over time, Church leaders have come to see tourism to Temple Square and its other historic sites in the United States as an avenue for outreach and proselytization (Hudman and Jackson 1992;Olsen 2006b, in press(b); Olsen and Timothy 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Founded by Brigham Young after relocating the Latter-day Saint Church to the Utah Basin (Arrington 1958), Temple Square has, in combination with the surrounding city blocks, become the administrative and spiritual centre of The Church of Jesus Christ of Latter-day Saints (see Figure 1). Despite the many historical changes to the landscape and organization of Temple Square and its surroundings (see Jackson 1994;Jackson and Bryson 2003;Olsen 2009; Parer a 2005), the function and goals of Temple Square have remained the same since the early twentieth century: to be an effective public relations and missionary tool for the Latter-day Saints Church (Dockstader 1992; see Olsen 2008Olsen , 2009). …”
Section: Temple Square Case Studymentioning
confidence: 98%
See 1 more Smart Citation
“…The Ganges River, St Peter's Basilica, the Salt Lake Temple, Borobudur and Prambanan, Angkor Wat, Old Jerusalem, the Taj Mahal and the Baha'i Gardens are world-class examples of attractions for religious and secular tourists (Collins-Kreiner & Gatrell, 2006;Olsen, 2009;Shinde, 2008). However, it should be noted that not all sacred sites that appeal to religious adherents and pilgrims necessarily entice general cultural tourists.…”
Section: Introductionmentioning
confidence: 94%
“…Examples from the first and second interpretative paradigms can be found in all three denominations, as the decision regarding the strategy of the interpretation (and in general public outreach) remains at the discretion of the local diocese. It is not unusual that because of the rigid hierarchical management structures of churches, site managers (comprised of professional clergy usually not trained in tourism) rely on ecclesiastical management structures largely unaffected by modern management trends (Olsen 2009). However, the research revealed that examples of the postmodern third paradigm are to be found predominantly in the Anglican churches of the United Kingdom.…”
Section: Recognition and Reconciliationmentioning
confidence: 96%